(untitled) (Nonconventional Technologies Review, 2020)
The scientific paper proposes a pragmatic perspective of presenting some theoretical and practical aspects regarding the place and role of information technology in an industrial organization that uses processing with nonconventional technologies, more precisely processing by electrical erosion. The implementation of an information system within the organization allows the acquisition, access, storage, and transmission of information more and more easily. Properly implemented computerization comes with two benefits in the organization’s activities: it increases the quality of services and reduces costs. For an overview, general aspects of nonconventional technologies were also presented, focusing on electrical erosion processing. The point of view presented is only a small part of the possibilities of implementing information technology, an information system, so improvements can be obtained in the production process by processing by electrical erosion.